Deconstructing the Infrastructure: A Complex History of Diachronous Metamorphism and Progressive Deformation during the Late Cretaceous to Eocene in the Thor-Odin–Pinnacles Area of Southeastern British Columbia - van Rooyen, D.; Carr, S. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
SUMMARYThe Thor-Odin dome is a basement-cored tectonothermal culmination in southern British Columbia containing high-grade metamorphic rocks that were polydeformed in the Late Cretaceous to Eocene. The rocks south of the Thor-Odin dome that extend ca. 20 km to the Pinnacles culmination and Whatshan batholith comprise a heterogeneous tract of polydeformed medium- to high-grade metamorphic rocks and host the South Fosthall pluton near the base of the structural section. They lie in the footwall of the Columbia River fault (CRF) zone, a moderately east-dipping, ductile-brittle, normal fault that was active after ca. 55 Ma and reactivated periodically up to 30 Ma. This tract of rocks has been interpreted as a midcrustal zone that was exhumed and cooled during Eocene extension or, alternatively, a mid-crustal channel that was bounded at the top by the CRF and was active during the Late Cretaceous to Eocene. However, the timing of metamorphism, deformation, anatexis in basement rocks, and intrusion of leucogranite plutons reveals that there are four tectonothermal domains within the tract that each experienced metamorphism, deformation and cooling at different times. These rocks record Cretaceous metamorphism and cooling in the upper structural levels and three stages of progressive metamorphism and penetrative deformation that migrated into deeper crustal levels in the Paleocene and Eocene producing a complex structural section that was exhumed in part due to motion on the Columbia River fault zone, and in part due to NE-directed transport over a basement ramp.